A visual analysis of Malay wood carving motifs in Istana Lama Seri Menanti, Negeri Sembilan / Noor Aisyah Omar - Omar, Noor Aisyah (2014)
Malaysia is a country that has a lot of wood where there are about 3000 species of wood in the country. Wood carving is significant craft in the Malay architecture ofthe former Pattani region stretching from north-eastern states of Peninsular Malaysia to southern province of Thailand (Ismail Said, 2001). Two Malay craftsmen named Kahar and Taib was carved the wood in Istana Lama Seri Menanti. The craftsman named Kahar was awarded the title of Dato' Panglima Sultan by Tuanku Muhammad for his services. (Arkib Negara Malaysia, 2013). In Malay woodcarvings, the main categories of motifs popularly used are flora, fauna, geometry, calligraphy, cosmic and mystical Istana Lama Seri Menanti was built in 1905 and complete at 1908. They have 99 pillar that represent 99 juak-juak hulubalang Negeri Sembilan and 4 pillar in the middle is represent Empat Orang Besar Istana (Orang Empat Istana). It has 55 to 60 motif of wood carving in Istana Lama Seri Menanti include the pillar, door and windows. From 99 pillar, 52 pillar have a woodcarving all motifs are different in each pillar. Wood carving in Istana Seri Menanti Negeri Sembilan is a tradition that we need to preserve for young generation for they to know the origin and uniqueness tradition in Negeri Sembilan. The different about the motif is part of their creativity when their build that palace. All the motif in the wood carving is also have their own meaning and used for their tradition.